2022
DOI: 10.1021/acs.energyfuels.1c04186
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Pyrolysis–Nonthermal Plasma/Catalytic Reforming of Waste Plastic over Different Catalyst Support Materials

Abstract: A two-stage pyrolysis–nonthermal plasma/catalytic steam reforming reactor system was used to produce hydrogen from waste high-density polyethylene in relation to different catalyst support materials. The catalyst support materials investigated were MCM-41, Y-zeolite, ZSM-5, Al2O3, TiO2, dolomite, BaTiO3, CaTiO3, and Mo2C. Some of the materials suppressed the generation of plasma, while others enhanced it by improving the generation of microdischarges and surface discharges. Among the tested materials, MCM-41 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…FACs and BFCs can be used in gasification and HTL, as well. , FHCs and BFCs are more effective in hydropyrolysis processes to obtain linear alkanes that are useful in fuel production . Moreover, FACs, FHCs, and BFCs can be used with advanced energy sources, like microwave and plasma to increase conversions and product selectivity. Some researchers even used light and electrical energy sources for catalytic thermolysis.…”
Section: Chemical Recycling Of Posmentioning
confidence: 99%
“…FACs and BFCs can be used in gasification and HTL, as well. , FHCs and BFCs are more effective in hydropyrolysis processes to obtain linear alkanes that are useful in fuel production . Moreover, FACs, FHCs, and BFCs can be used with advanced energy sources, like microwave and plasma to increase conversions and product selectivity. Some researchers even used light and electrical energy sources for catalytic thermolysis.…”
Section: Chemical Recycling Of Posmentioning
confidence: 99%
“…Hydrogen (H 2 ) is an important precursor in many quality improvement processes and is likely to be used as a clean fuel in the future, such as in H 2 power plants and fuel cell power plants. However, H 2 is predominantly produced from fossil fuels, which are nonrenewable. The development of H 2 production from renewable fuels or waste materials is an interesting option to promote the sustainability of H 2 -based energy.…”
Section: Introductionmentioning
confidence: 99%
“…In these integrated processes, plasma-mediated processes can be foreseen as a means for chemical energy storage by using the excess electricity from the renewable energy sources, to produce chemicals from plastic waste deconstruction with long-term storage without the additional release of CO 2 . Inside a plasma environment, a large variety of excited and dissociated species are generated, and by colliding with each other on an active surface (catalyst), targeted products can be obtained. , Despite these benefits, the application of non-thermal plasma to plastic waste deconstruction has not been well understood yet as only several studies have recently reported on plasma only and plasma catalysts. These reports focus on the production of hydrogen from HDPE decomposition. However, other light hydrocarbons (C 1 –C 4 ), used as basic energy feedstocks and as commodity organic compounds to produce many industrially essential chemicals, have been overlooked so far.…”
Section: Introductionmentioning
confidence: 99%